Cardiac remodeling in normotensive pregnancy and in pregnancy complicated by hypertension: systematic review and meta‐analysis. (4th December 2017) - De Haas, S.; Ghossein‐Doha, C.; Geerts, L.; van Kuijk, S. M. J.; van Drongelen, J.; Spaanderman, M. E. A.
ABSTRACT: Objective: The aim of this systematic review and meta‐analysis was to describe comprehensively the pattern of cardiac remodeling during normotensive human singleton pregnancy and to compare it with that of pregnancy complicated by hypertension. Methods: We performed a meta‐analysis of the current literature on cardiac remodeling during normotensive and complicated pregnancies. Literature was retrieved from PubMed (NCBI) and EMBASE (Ovid) databases. Included studies needed to report a reference measurement (matched non‐pregnant control group, prepregnancy or postpartum) and measurements made during predetermined gestational‐age intervals. Mean differences between reference and pregnancy data were calculated using the random‐effects model described by DerSimonian and Laird. Results: Forty‐eight studies were included in the meta‐analysis, with publication dates ranging from 1977 to 2016. During normotensive pregnancy, most geometric indices started to increase in the second trimester. Left ventricular mass (LVM) increased by 28.36 (95% CI, 19.73–37.00) g (24%), and relative wall thickness (RWT) increased by 0.03 (95% CI, 0.02–0.05) (10%) compared with those in the reference group. During hypertensive pregnancy, LVM and RWT increased more than during normotensive pregnancy (92 (95% CI, 75.46–108.54) g (95%) and 0.14 (95% CI, 0.09–0.19) (56%), respectively). Conclusions: During normotensive pregnancy, most cardiac geometric indices change from the second trimester onwards. Both LVM and RWT increase, by 20% and 10%, respectively, consistent with concentric rather than eccentric remodeling. Cardiac adaptation in hypertensive pregnancy deviates from that in healthy pregnancy by a greater change in LVM (95% increase from reference) and RWT (56% increase from reference). Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.